2017
DOI: 10.1016/j.jbi.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perception of alternative displays of clinical research evidence for clinical decision support – A study with case vignettes

Abstract: Objective To design alternate information displays that present summaries of clinical trial results to clinicians to support decision-making; and to compare the displays according to efficacy and acceptability. Methods A 6-between (information display presentation order) by 3-within (display type) factorial design. Two alternate displays were designed based on Information Foraging theory: a narrative summary that reduces the content to a few sentences; and a table format that structures the display according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our study findings add to the growing evidence supporting alternative information display formats to convey the gist of clinical studies [11][12][13][14][15][16][17][18][19][20][21][22], suggesting that the standard format of scientific reporting, especially for article abstracts, is worth reconsidering. The ideal abstract display format should match clinicians' mental model to reduce cognitive workload in interpreting clinical study results.…”
Section: Implications For the Reporting Of Rctsmentioning
confidence: 56%
See 3 more Smart Citations
“…Our study findings add to the growing evidence supporting alternative information display formats to convey the gist of clinical studies [11][12][13][14][15][16][17][18][19][20][21][22], suggesting that the standard format of scientific reporting, especially for article abstracts, is worth reconsidering. The ideal abstract display format should match clinicians' mental model to reduce cognitive workload in interpreting clinical study results.…”
Section: Implications For the Reporting Of Rctsmentioning
confidence: 56%
“…All participants received a $100 incentive to participate in the study sessions. A previous study with similar design [22] demonstrated that 20 participants are enough to detect a moderate difference between interactive visual displays and narrative display with a power of 0.80.…”
Section: Participant Recruitmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Overall, we hypothesized that interactive visual displays would reduce clinicians’ cognitive workload in interpreting RCTs compared with narrative RCT abstracts. Building on Slager et al’s exploratory study on static tabular displays [ 22 ], we employed information foraging theory [ 23 ] and information visualization techniques to design a high-fidelity prototype with interactive visual displays of RCT results. The information displays were designed to help clinicians rapidly review, synthesize, and compare the results of relevant RCTs for the treatment of a specific patient.…”
Section: Introductionmentioning
confidence: 99%